Interactions between deforestation and atmospheric composition on the climate of Amazônia and Cerrado and their consequences to agriculture - Abrahão, Gabriel Medeiros (2021)
razilian crop production has managed to grow expressively in the last 15 years with relatively little conversion of natural vegetation. Deforestation in the major Brazilian biomes however is still far from zero, and rates have been going up with the recent dismantling of public environmental governance (EG). Deforestation leads to changes in regional climate, which along with global climate change affects crop yields, often negatively. EG can benefit production by minimizing these effects. This thesis investigates how interactions between deforestation-induced and global climate change can affect Brazilian double cropping systems. These systems in Brazil play an important role on global grain production. Although modelling studies have suggested that they can be severely affected by global climate change, there’s little empirical understanding of their sensitivity to climate. Chapter 1 examines how past climate variability affected municipality-level statistics of soybeans and second crop maize yields and double cropping adoption, and evaluate the impacts of projected global changes in climate. Double cropping in parts of Brazil with strong precipitation seasonality is more likely to occur when the rainy season is larger than 200 days, with no DC in municipality-years below 150 days. CMIP6 models project years with the rainy season shorter than 200 days to be more likely by 2035-2050 under the SSP2-4.5 scenario in key double cropping regions in central Brazil. Soybean yields are projected to decline by ~12%, a result that is not substantially affected by yield model specification. Second crop maize yields are found to be less sensitive to changes in climate than soybeans, with no significant impacts on the country average. However, models that explicitly account for vapor pressure deficit project substantial (>10%) impacts on second crop maize yields in regions with projected rainy season shortening. Chapter 2 uses a fully coupled climate system model and the empirical yield models from Chapter 1 to evaluate how different plausible EG futures can affect the Brazilian production of soybeans and 2nd crop maize. We perform simulations combining two land use scenarios representing different levels of EG and two global climate change scenarios (RCPs 2.6 and 8.5). We find that soybean yields are negatively affected in all scenarios, but differences in EG can impact yields as much as differences in atmospheric composition (RCPs). Stronger environmental governance can prevent soybean production losses equivalent to 442-527 million USD year -1 in the Amazon and 670-1347 million USD year -1 in the Cerrado by 2050, up to 10% of projected production. Collectively, Brazilian soybean farmers have much to gain with better environmental governance and it would be in their interest to enforce and even extend private zero-deforestation agreements in the Amazon and Cerrado biomes. Keywords: Double cropping. Statistical crop model. Climate change. Brazil. Deforestation. Biogeophysical climate change. Land use and land cover change. Earth system models